(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2021)
This work results from the implementation of Praxis, Reflection and Action in a participatory way, among students and teachers of the last years of agrotechnical schools, with students and researchers from the Faculty of Veterinary Sciences, through the study of emergent properties from a sheep population. It was developed based on bonding all the actors, starting from a problem situation, promoting critical and collaborative efforts that encourage the acquisition of skills to intervene in real productive situations of their community. The university extension promotes the expansion of experiences taking them to the field and allows an enrichment of learning. For members of the university environment, continuous training also means exposing themselves to the reality of their discipline, beyond the classroom and conferring the knowledge acquired to a part of society, understanding that through teaching it is also possible to learn.